Análisis cuantitativo de los rasgos de identidad percibidos por los ciudadanos lojanos - Fierro Cueva, Jehocasta Cecibel (2014)
With the overall objective of determining the characteristics, social and cultural elements that are assumed to be representative of the identity of Loja. A literature study on the identity, brand and the city was made; gathering information and comparing authors set as primary axis of research, as is the guidance to define and know what is a Brand City. Analyzed and interpreted the information obtained from the survey of 370 city residents Loja to define the social and cultural elements, allowing approve the hypothesis: "there are some features icons and characters Lojanos assume as more representative of the city and that can be integrated into the projection of their cultural identity through a trademark". The results based on 29 survey questions were analyzed quantitatively, allowing meet one of the specific objectives: perform quantitative study to define social and cultural elements Lojanos identified as the most representative of city. Finally conclusions and recommendations were made.